Evaluation of Rashd Al-Qiblah Method Accuracy: Spherical Plane And Ellipsoid Approaches in Qibla Direction Determination - Helmi, Rahman; Badrian, H. (Indonesian Journal of Religion and Society, 2024)
Determination of Qibla direction is an important aspect in the implementation of Muslim worship. One of the methods used is rashd al-qiblah, which is a direct observation based on the shadow of an object when the sun is directly above the Kaaba. However, the use of rashd al-qiblah that considers the shape of the Earth's ellipsoid through Vincenty Theory is still very limited. This study aims to analyze the accuracy of determining the Qibla direction using two geometric approaches, namely the spherical plane and the ellipsoid, and compare it with the results of direct observation using the rashd al-qiblah method. The research location is focused on Banjarmasin, which is geographically qualified to use the rashd al-qiblah method. The results of this study are expected to provide a comprehensive picture of the differences in accuracy between the two calculation methods and the direct observation method. The analysis also aims to evaluate the reliability of the ellipsoid-based method in the context of Qibla direction determination practice. The findings of this study can be an important reference for phalacticians and the general public in choosing the most accurate method for Qibla direction determinatio